Effects of rapid thermal annealing on the optical properties of low-loss 1.3 μm GalnNAs/GaAs saturable Bragg reflectors - Gundogdu, K. (2009)
We report studies of the effect of rapid thermal annealing (RTA) on the optical properties of a low-loss 1.3 mum saturable Bragg reflector (SBR), consisting of a GaInNAs/GaAs single quantum well embedded in an AlAs/GaAs Bragg reflector grown monolithically on a GaAs substrate. RTA gives rise to a blueshift of the photoluminescence (PL) peak (and therefore of the excitonic absorption peak) and an enhancement of PL intensity, while the reflectivity properties including peak reflectivity and bandwidth are not degraded. Temperature dependent photoluminescence measurements show that the RTA-induced blueshift of photoluminescence consists of two components: one originating from the increase of optical transition energies and another from the reduction of carrier localization. Time-resolved photoluminescence results at room temperature provide information about the recombination dynamics of carriers directly relevant to the application of the SBR in laser mode locking.